OCEANOGRAPHIC CHARACTERISTICS OF KLABAT BAY, BANGKA ISLAND, INDONESIA - Sachoemar, Suhendar I.; Kristijono, Agus; Yanagi, Tetsuo (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
The oceanographic characteristics of Klabat Bay in Bangka Island of Indonesia were investigated by using a series of temperature, salinity, turbidity, TSS (total suspended solid), transparency, DIN (Dissolved Inorganic Nitrogen), DIP (Dissolved Inorganic Phosphorus), DO (Dissolved Oxygen) and chlorophyll-a data in the wet season (Northwest Monsoon) and dry season (Southeast Monsoon) of 2003, respectively. The observation results show that the hydro-oceanographic characteristics of Klabat Bay in the inner part and the outer part of the bay were dominantly influenced by the terrestrial and oceanic environment, respectively. High precipitation during the wet season decreased salinity, DO and transparency and increased total suspended solid (TSS), turbidity, DIN and chlorophyll-a within the bay. The reverse occurred during the dry season, except DIP.